TFIIB co-localizes and interacts with α-tubulin during oocyte meiosis in the mouse and depletion of TFIIB causes arrest of subsequent embryo development. - Hui Liu (Public Library of Science (PLoS), 2013)
TFIIB (transcription factor IIB) is a transcription factor that provides a bridge between promoter-bound TFIID and RNA polymerase II, and it is a target of various transcriptional activator proteins that stimulate the pre-initiation complex assembly. The localization and/or attachment matrix of TFIIB in the cytoplast is not well understood. This study focuses on the function of TFIIB and its interrelationship with α-tubulins in a mouse model. During oocyte maturation TFIIB distributes throughout the entire nucleus of the germinal vesicle (GV). After progression to GV breakdown (GVBD), TFIIB and α-tubulin co-localize and accumulate in the vicinity of the condensed chromosomes. During the MII stage, the TFIIB signals are more concentrated at the equatorial plate and the kinetochores. Colcemid treatment of oocytes disrupts the microtubule (MT) system, although the TFIIB signals are still present with the altered MT state. Injection of oocytes with TFIIB antibodies and siRNAs causes abnormal spindle formation and irregular chromosome alignment. These findings suggest that TFIIB dissociates from the condensed chromatids and then tightly binds to microtubules from GVBD to the MII phase. The assembly and disassembly of TFIIB may very well be associated with and driven by microtubules. TFIIB maintains its contact with the α-tubulins and its co-localization forms a unique distribution pattern. Depletion of Tf2b in oocytes results in a significant decrease in TFIIB expression, although polar body extrusion does not appear to be affected. Knockdown of Tf2b dramatically affects subsequent embryo development with more than 85% of the embryos arrested at the 2-cell stage. These arrested embryos still maintain apparently normal morphology for at least 96h without any obvious degeneration. Analysis of the effects of TFIIB in somatic cells by co-transfection of BiFC plasmids pHA-Tf2b and pFlag-Tuba1α further confirms a direct interaction between TFIIB and α-tubulins.